The effect of eradaicating helicobacter pylori infection on intragastric pH and serum gastrin concentrations - İrfan SOYKAN; Ali ÖZDEN; Yusuf UZUN; Hülya ÇETİNKAYA; Ali Reşit BEYLER; Kadir BAHAR; Nihat SİPAHİ; Özden UZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2019)
-